Pengaruh Pemanfaatan Aplikasi Google Classroom Terhadap Hasil Belajar Siswa di SMK Kartika 1-2 Padang (Study Mata Pelajaran Jurusan Otomatisasi Dan Tata Kelola Perkantoran Pada Saat Daring) - Fitri Fitri; Armida S (Jurnal Salingka Nagari, 2022)
The raw data types obtained by distributing questionnaires in the form of Google Sheets to X, XI and XII office management automation students at SMK Kartika 1-2 Padang have specified criteria. The results show that the use of the Google Classroom app and the benefits of the Google Classroom app simultaneously have a significant impact on student learning outcomes. using the Google Classroom app had a huge positive impact on learning outcomes. Between students , the benefits of the Google Classroom app had a positive and significant impact on student learning outcomes. The use and benefits of the Google Classroom app had a 24% impact on student learning outcomes in the Department of Office Automation and Control, Department of Office Automation and Control, SMK Kartika 1-2 Padang.